Identifying Parental Learning Assistance for Children with Disabilities During COVID-19 Pandemic - Hendriani, Wiwin (Indonesian Journal of Disability Studies, 2023)
This research was motivated by the many difficulties and problems faced by parents of children with disabilities in accompanying their children to study at home during the Covid-19 pandemic. Difficulties with learning assistance faced by parents of children with disabilities, if not immediately addressed, will have long-lasting impacts and give rise to other problems, such as children becoming increasingly hampered in mastering learning goals, lack of discipline, and the emergence of various new habits and behavior patterns in children that are less adaptive. The participants in this research were 20 parents of children with disabilities, consisting of 8 mothers of children with intellectual disabilities and 12 mothers of children with an autism spectrum disorder. This research approach is a qualitative case study. The data mining method uses focused group discussion, observation, and online interviews. The collected data was analyzed using inductive thematic analysis. The results of data analysis found 14 themes regarding the steps taken by parents in assisting children's learning. The 14 themes were then categorized into 3 groups of assistance based on their objectives. These results can be used as a basis for formulating strategies to empower parents of children with other disabilities, in optimizing their involvement in the child's learning process.